R2 and R2* are equally effective in evaluating chronic response to iron chelation. Issue 5 (3rd March 2014) - Wood, John C.; Zhang, Pinggao; Rienhoff, Hugh; Abi‐Saab, Walid; Neufeld, Ellis
<x xml:space="preserve">Abstract</x> MRI relaxometry (R2, R2*) has generally replaced liver biopsy for estimation of liver iron stores in response to iron chelation, but there have been no longitudinal studies comparing R2 and R2* techniques. We use R2 and R2* liver iron concentration (LIC) estimates, transfusional iron burdens, and drug compliance data to calculate iron chelation efficiency (ICE) in patients undergoing a Phase II trial of SPD602. Fifty‐one patients underwent a baseline examination, 39 patients completed 1 year, and 26 patients completed 2 years. Baseline LICR2 and LICR2* estimates were unbiased, but had limits of agreement exceeding 50%, suggesting that these techniques cannot be interchanged with one another in the same patient. However, ICE estimates across the two techniques compared more favorably, with r2 values reaching 0.89 at 2 years. 95 confidence intervals for efficiency estimates were 0.0 ± 4.1%. These data indicate that clinical trial and clinical effectiveness data calculated using LICR2 and LICR2* estimates can be compared to one another, even though LIC estimates may be disparate on cross‐sectional analysis. While the choice of MRI assessment technique for clinical trials and for clinical management depends on many logistical considerations, one can have confidence comparing conclusions on clinical effectiveness. Am. J. Hematol. 89:505–508, 2014. © 2014 Wiley Periodicals, Inc.